2015
DOI: 10.1002/elsc.201400203
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymers made from methane in bioreactors

Abstract: Methane (CH4) is a potent greenhouse gas and mitigation is important to reduce global warming impacts. In this study, we aimed to convert CH4 to polyhydroxybutyrate (PHB; a biopolymer) by enrichment of methanotrophic consortia in bioreactors. Two different methanotrophic consortia were established form landfill top‐cover (landfill biomass [LB]) and compost soils (compost biomass [CB]), through cultivation under CH4:CO2:air (30:10:60) in batch systems. The established cultures were then used as inoculi (0.5 g L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 90 publications
(184 reference statements)
0
3
0
Order By: Relevance
“…At their end life, these bioplastics are degraded back to CO 2 to produce a closed cycle . However, this process is associated with high energy and cost demands (30–50% of the production cost) associated with the cultivated crops , . Therefore, developing a new reliable feedstock with a cheaper production process, such as wastewater, biogas methane and carbon dioxide, is a key milestone in the scale up of biopolymers production.…”
Section: Introductionmentioning
confidence: 99%
“…At their end life, these bioplastics are degraded back to CO 2 to produce a closed cycle . However, this process is associated with high energy and cost demands (30–50% of the production cost) associated with the cultivated crops , . Therefore, developing a new reliable feedstock with a cheaper production process, such as wastewater, biogas methane and carbon dioxide, is a key milestone in the scale up of biopolymers production.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of bacterial consortia of methanotrophs and het-erotrophs have been noted, for example, in the production of microbial proteins by methanotrophs [30,83]. Other researchers have demonstrated that consortia are more efficient than pure cultures in the production of valuable compounds e.g., polymers (PHAs) [84,85] or ectoine [86]. The presence of heterotrophs ensures culture stabilization by consuming potentially inhibitory metabolic byproducts or contaminants [87].…”
Section: The Importance Of Microorganism Community In Biotechnologymentioning
confidence: 99%
“…There are a great many studies that have explored the relative merits of mixed cultures versus pure strains for PHA accumulation in general, including some that are specific to the use of methane as a carbon source [ 14 , 58 , 70 , 91 , 92 , 93 , 94 ]. Overall, these studies suggest that such mixed cultures may provide specific benefits such as: co-culture bacteria removing potentially toxic byproducts (e.g., methanol or formaldehyde) from the medium; beneficial nutrients being supplied by co-culture bacteria; operation under non-sterile conditions; and even possibly higher yields and production rates.…”
Section: Process Conditions For Phb Production From Methanementioning
confidence: 99%